Design of a low-cost, portable electronic device for the estimation of reaction forces generated during walking from foot-ground contact - Guevara, Nelson Eduardo
This paper presents a low-cost electronic system designed to estimate ground reaction forces (GRF). The system consists of a master node and two slave nodes. The master node sends instructions to its slave nodes, and each slave node consists of two electronic boards that sample and store data from two force templates. These templates are equipped with 14 FlexiForce A301 piezo-resistive sensors (FSR). To capture the movements, slave nodes are attached to the feet of each participant. Subsequently, the "Start" command is transmitted via the master node, which is connected to the USB port of a personal computer (PC). Once the walking session is over, the information collected by the slave nodes can be downloaded by accessing the Access Point generated by these devices via Wi-Fi connection. The proposed system for GRF estimation was validated using force platforms (BTS Bioengineering P6000, Italy), giving an error equal to 15.04 %.